Analisis Penerapan Prinsip-Prinsip Syariah Pada Perjanjian Asuransi Syariah (Studi Kasus PT. Sun Life Financial Syariah Cabang Medan) - Pohan, Komariah Hapni; Sudiarti, Sri; Inayah, Nurul (Jurnal Manajemen Akuntansi (JUMSI), 2024)
The emergence of Islamic insurance raises many questions about what differentiates Islamic insurance from conventional insurance. The purpose of this study was to analyze the application of sharia principles in the insurance agreement of PT. Sun Life Financial Syariah. Islamic insurance is a big question among Muslims regarding the mechanisms that exist in Islamic insurance. As for sharia principles, it is a differentiator from conventional insurance. The main principle applied to sharia insurance is mutual help. PT. Sun life sharia financial has implemented sharia principles in sharia insurance agreements and in the tabarru fund management mechanism according to Islamic sharia. In this study the authors used a descriptive qualitative method by collecting data and information through interviews, observation and documentation. From the results of the analysis, these nine principles are the principle of monotheism, the principle of justice, the principle of mutual help, the principle of cooperation, the principle of trust, the principle of willingness, the principle of the prohibition of usury, the principle of the prohibition of maisir and the principle of the prohibition of gharar. these nine principles have been applied to the Medan branch of PT. Sun life financial sharia and are in accordance with the basic principles of sharia insurance. Tabarru fund management at PT.Sun life financial syariah Medan branch is also in accordance with sharia principles.